Building Leadership, Capacity, and Power to Advance Health Equity and Justice through Community‐Engaged Research in the Midwest. Issue 1 (11th October 2020) - Woods‐Jaeger, Briana; Daniel‐Ulloa, Jason; Kleven, Lauren; Bucklin, Rebecca; Maldonado, Adriana; Gilbert, Paul A.; Parker, Edith A.; Baquero, Barbara
Abstract: The Health Equity Advancement Lab (HEAL) at the University of Iowa College of Public Health began in 2012 to support students, researchers, and community members interested in tackling persistent health inequities through a community‐based participatory research (CBPR) approach. Using concepts from critical consciousness theory, we developed an approach to building students', faculty members', and community partners' capacity to engage in CBPR to promote health equity that involved immersion in developing CBPR projects. Our paper describes the evolution of HEAL as a facilitating structure that provides a support network and engages diverse stakeholders in critical reflection as they participate in research to advance health equity, and resulting political efficacy and social action. We describe one HEAL‐affiliated research project that employs a CBPR approach and has a strong focus on providing transformative learning experiences for students, faculty, and community members. We highlight challenges, successes, and lessons learned in the application of critical consciousness as a framework that engages diverse academic and community partners seeking to promote health equity. We argue that critical consciousness is a relevant theoretical framework to promote transformative learning among students, faculty, and community partners to promote health equity research in diverse communities. Highlights: This paper describes the development and evolution of the Health Equity Advancement Lab (HEAL). HEAL emphasizes transformative learning opportunities for students, faculty and community partners. HEAL is guided by community‐based participatory research principles & critical consciousness theory HEAL creates a support network to promote health equity research in diverse communities. We describe one HEAL‐affiliated CBPR study that exemplifies transformative learning experiences.